2017
DOI: 10.1016/j.pestbp.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Target-site and non-target-site resistance mechanisms to ALS inhibiting herbicides in Papaver rhoeas

Abstract: Target-site and non-target-site resistance mechanisms to ALS inhibitors were investigated in multiple resistant (tribenuron-methyl and 2,4-D) and only 2,4-D resistant, Spanish corn poppy populations. Six amino-acid replacements at the Pro197 position (Ala197, Arg197, His197, Leu197, Thr197 and Ser197) were found in three multiple resistant populations. These replacements were responsible for the high tribenuron-methyl resistance response, and some of them, especially Thr197 and Ser197, elucidated the cross-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 38 publications
5
68
0
Order By: Relevance
“…There are biotypes of corn poppy resistant to ALS‐inhibiting and phenoxy‐carboxylate herbicides that can degrade imazamox . It is unknown whether the same cytochrome P450 degrades herbicides with these modes of action or if other enzymes could be involved.…”
Section: Mechanisms Of Synthetic Auxin Herbicide Resistance In Well‐cmentioning
confidence: 99%
See 1 more Smart Citation
“…There are biotypes of corn poppy resistant to ALS‐inhibiting and phenoxy‐carboxylate herbicides that can degrade imazamox . It is unknown whether the same cytochrome P450 degrades herbicides with these modes of action or if other enzymes could be involved.…”
Section: Mechanisms Of Synthetic Auxin Herbicide Resistance In Well‐cmentioning
confidence: 99%
“…There are biotypes of corn poppy resistant to ALS-inhibiting and phenoxy-carboxylate herbicides that can degrade imazamox. 20 It is unknown whether the same cytochrome P450 degrades herbicides with these modes of action or if other enzymes could wileyonlinelibrary.com/journal/ps be involved. The herbicide, 2,4-D, was found to induce glycoside hydrolase (GH3) and glutathione S-transferase (GST3) expression in susceptible and resistant P. rhoeas plants, thus increased expression of these enzymes did not appear to be involved in resistance to 2,4-D. 21 There is a need to identify the genes and to more fully understand the mechanisms involved in corn poppy herbicide resistance.…”
Section: Corn Poppy (Papaver Rhoeas)mentioning
confidence: 99%
“…Chlorsulfuron inhibit acetolactate synthase (ALS) which is a important enzyme in the biosynthesis of valine, leucine and isoleucine. A previous study reported that a high level of resistance in plants is due to substitutions at Pro197 to sulfonylurea herbicides (Rey-Caballero et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These populations displayed a survival of >90% at the recommended field dose (480 g ai ha −1 ) for Amaranthus hybridus, Hirschfeldia incana and Parthenium hysterophorus, or at 600 g ai ha −1 for Conyza canadensis and Papaver rhoeas, while it was~25% for Conyza sumatrensis (data not shown). 2,4-D S populations belonging to these species were originally harvested from areas close to the fields evolving resistance to this herbicide, except for P. rhoeas in which a known S standard was used [13,27]. Seeds were maintained at 4 • C in a cold chamber and they had more than an 80% germination rate during this study.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The plants were harvested at 96 HAT. Previous experiments with different dicotyledonous weeds, such as P. rhoeas, established this time point to be the most suitable for finding maximum differences between S and R populations to SAH [13,27,30,31]. The unabsorbed 14 C-herbicide was removed from the treated leaf with a water-acetone solution (1:1 v/v) by washing the plants three times separately with 1 mL of that solution.…”
Section: C-24-d Absorption and Translocation In Dicotyledonous Weedsmentioning
confidence: 99%